Community Policing in the Area of the Murska Sobota Police Directorate – Hand in Hand for a Safe Everyday Life - EMAN, KATJA; IVANČIĆ, DAMIR; BAGARI, DEJAN (Anali PAZU HD, 2024)
Community policing is a relatively newer, though not entirely novel, approach to ensuring security. This paper aims to present the research findings conducted within the Murska Sobota Police Directorate, focusing on interviews with the heads of police districts in both rural and urban areas of the Pomurje region. The results obtained affirm prior conclusions, indicating that in urban areas, approximately two-thirds of the residents are unfamiliar with the head of the police district. Consequently, mutual cooperation between residents and the police tends to be less effective compared to rural areas. In the conclusion, we explore potential strategies to enhance the current situation in Pomurje.
Keywords: community policing; security; rural environment; urban environment; Murska Sobota Police Directorate